Faster Movement Speed Results in Greater Tendon Strain during the Loaded Squat Exercise - Earp, Jacob E.; Newton, Robert U.; Cormie, Prue; Blazevich, Anthony J. (Frontiers in Physiology, 2016)
Introduction: Tendon dynamics influence movement performance and provides the stimulus for long-term tendon adaptation. As tendon strain increases with load magnitude and decreases with loading rate, changes in movement speed during exercise should influence tendon strain. Methods: Ten resistance-trained men [squat one repetition maximum (1RM) to body mass ratio: 1.65 ± 0.12] performed parallel-depth back squat lifts with 60% of 1RM load at three different speeds: slow fixed-tempo (TS: 2-s eccentric, 1-s pause, 2-s concentric), volitional-speed without a pause (VS) and maximum-speed jump (JS). In each condition joint kinetics, quadriceps tendon length (LT), patellar tendon force (FT) and rate of force development (RFDT) were estimated using integrated ultrasonography, motion-capture and force platform recordings. Results: Peak LT, FT, and RFDT were greater in JS than TS (p<0.05), however no differences were observed between VS and TS. Thus, moving at faster speeds resulted in both greater tendon stress and strain despite an increased RFDT, as would be predicted of an elastic, but not a viscous, structure. Temporal comparisons showed that LT was greater in TS than JS during the early eccentric phase (10-14% movement duration) where peak RFDT occurred, demonstrating that the tendon’s viscous properties predominated during initial eccentric loading. However, during the concentric phase (61-70% & 76-83% movement duration) differing FT and similar RFDT between conditions allowed for the tendon’s elastic properties to predominate such that peak tendon strain was greater in JS than TS. Conclusions: Based on our current understanding, there may be an additional mechanical stimulus for tendon adaptation when performing large range-of-motion isoinertial exercises at faster movement speeds.